An analysis of the risk of perioperative ischemic stroke in patients undergoing non-cardiovascular and non-neurological surgeries. (2nd January 2020) - Wang, Yun; Qin, Wei; Hu, Wenli
ABSTRACT: Objectives : This study aimed to assess the preoperative risk factor for perioperative ischemic stroke (PIS) in patients undergoing non-cardiovascular and non-neurological surgeries. Methods : Patients were retrospectively enrolled and grouped into two groups at a ratio of 1:2 according to their PIS status, i.e. patients with PIS in disease group, and patients without PIS in control group. Univariate analysis and multivariate logistic regression analysis were performed on admission laboratory test indices and preoperative risk factors for stroke. The pooled cohort equation (PCE), Essen Stroke Risk Score (ESRS), and Stroke Prognostic Instrument II (SPI-II) were used to separately assess the risk of stroke in patients with or without a history of stroke. Results : There were significant differences between the two groups in the levels of high-density lipoprotein cholesterol (HDL-C), prealbumin, renal insufficiency, dyslipidemia, coronary heart disease, anemia, and hemoglobin; the incidence of electrolyte disturbance; and previous histories of smoking, drinking, and stroke. Multivariate logistic regression analysis showed that renal insufficiency, histories of smoking and stroke, and decreased HDL-C can increase the risk of PIS. There were no significant differences between the disease group and the control group in ESRS or SPI-II score in patients with stroke history. There was a significant difference between the two groups in the risk of PIS evaluated by PCE in patients without stroke history. Conclusions : History of stroke and smoking, renal insufficiency, and low HDL-C are independent risk factors for PIS. It is feasible to assess the risk of stroke in preoperative patients using PCE in clinical practice.